2021
DOI: 10.1038/s41467-021-23558-2
|View full text |Cite
|
Sign up to set email alerts
|

Cis-regulatory evolution spotlights species differences in the adaptive potential of gene expression plasticity

Abstract: Phenotypic plasticity is the variation in phenotype that a single genotype can produce in different environments and, as such, is an important component of individual fitness. However, whether the effect of new mutations, and hence evolution, depends on the direction of plasticity remains controversial. Here, we identify the cis-acting modifications that have reshaped gene expression in response to dehydration stress in three Arabidopsis species. Our study shows that the direction of effects of most cis-regula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…In order to differentiate these alternatives, the segregation of molecular variation within species can be used to infer the fitness effect of new mutations and quantify the strength of the evolutionary constraints imposed on the amino-acid sequence. We took advantage of a previous study, which determined the demographic history of the same two parental populations of A. lyrata 25,32 . We inferred the distribution of fitness effects (DFE) of new non-synonymous variants in these gene sets, following a method described in 25 that incorporates the specific demographic parameters of each population (Supplementary Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…In order to differentiate these alternatives, the segregation of molecular variation within species can be used to infer the fitness effect of new mutations and quantify the strength of the evolutionary constraints imposed on the amino-acid sequence. We took advantage of a previous study, which determined the demographic history of the same two parental populations of A. lyrata 25,32 . We inferred the distribution of fitness effects (DFE) of new non-synonymous variants in these gene sets, following a method described in 25 that incorporates the specific demographic parameters of each population (Supplementary Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…The contrasting global transcriptome responses of A. thaliana , E. salsugineum and A. hierochuntica to stress also emphasize the importance of generation and maintenance of new cis ‐acting elements in the adaptive evolution of plants to extreme habitats (Oh et al ., 2014 ; He et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that environmentally induced expression responses were highly consistent across our experimental plants, indicating that regulatory elements (both cis and trans ) are largely conserved between the three A. lyrata populations. Previous studies examining environmentally responsive genes have found that the regulatory conservation is frequently associated with the conservation of the gene product (He et al, 2021; Hodgins et al, 2016; Hunt et al, 2013; Lasky et al, 2014; Lowry et al, 2013; Zhang et al, 2017). Although our results qualitatively support these findings, as genes showing consistent expression responses to the environment (DEG ~ Field) were under stronger purifying selection than those showing genetically variable responses (DEG ~ Field:Population), we discovered that both gene sets exhibited stronger than expected signals of evolutionary constraint.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, plasticity in morphological, developmental, and physiological traits is thought to result from changes in gene expression (West-Eberhard, 2003), making the study of expression plasticity a promising approach for uncovering the genetic basis of phenotypic plasticity. Although studies of environmentally responsive genes have discovered a wide range of expression responses (Hodgins-Davis and Townsend, 2009), many populations and species have reacted consistently to environmental stress (He et al, 2021; Lowry et al, 2013; Wos et al, 2021a; Yeaman et al, 2014). As gene expression is primarily controlled by regulatory elements acting either in cis (affecting nearby genes) or trans (affecting distant genes), the conserved expression responses are indicative of conserved regulatory systems (Horvath et al, 2021; Lu et al, 2019; Rodgers-Melnick et al, 2016).…”
Section: Introductionmentioning
confidence: 99%